2022
DOI: 10.1111/omi.12386
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol strengthens probiotic effect of Limosilactobacillus reuteri in oral biofilms: A synergistic synbiotic approach

Abstract: Both in vitro and in vivo studies have shown that the probiotic Limosilactobacillus reuteri can improve oral health. Limosilactobacillus reuteri species are known to produce the antimicrobial “reuterin” from glycerol. In order to further increase its antimicrobial activity, this study evaluated the effect of the combined use of glycerol and Limosilactobacillus reuteri (ATCC PTA 5289) in view of using a synergistic synbiotic over a probiotic. An antagonistic agar growth and a multispecies biofilm model showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…In addition, since an antimicrobial substance such as reuterin would be expected to affect viability of the oral strains independent of pH, and in this study all the oral strains showed a high viability at pH 7.5 and pH 5.5, a major role for this substance in the effect appears unlikely. This is in agreement with a recent investigation which revealed that L. reuteri ATCC PTA5289 exerts probiotic effects on streptococci that are independent of reuterin [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, since an antimicrobial substance such as reuterin would be expected to affect viability of the oral strains independent of pH, and in this study all the oral strains showed a high viability at pH 7.5 and pH 5.5, a major role for this substance in the effect appears unlikely. This is in agreement with a recent investigation which revealed that L. reuteri ATCC PTA5289 exerts probiotic effects on streptococci that are independent of reuterin [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Limosilactobacillus reuteri strain ATCC PTA5289 has been shown to inhibit binding of S. mutans to saliva-coated surfaces [ 17 ] and a range of probiotic strains including L. reuteri ATCC PTA5289 and Lacticaseibacillus rhamnosus GG coaggregate with, and inhibit growth of, mutans streptococci [ [18] , [19] , [20] ]. More recently, challenge with cultures of live L. reuteri ATCC PTA5289, but not culture supernatants, has been demonstrated to reduce the cariogenic activity of in vitro biofilms [ 21 ] and addition of L. reuteri ATCC PTA5289 to a multispecies biofilm model significantly reduced S. mutans levels [ 22 ]. These results suggest that further investigation into potential mechanisms by which these probiotic strains could contribute to managing dental caries are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the increased production of reuterin by Limosilactobacillus reuteri from glycerol. 48 Hence, combining Limosilactobacillus reuteri with other active ingredients such as natural compounds or prebiotics may be a useful strategy for improving its antimicrobial efficacy. However, further details on this strategy need to be explored, including relevant references and future research perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for adjunctive periodontal treatments could be natural molecules. Among these natural molecules, polyphenols, probiotics and parabiotics are interesting as they can be used to reduce bacterial load and to control inflammation induced by oral pathogens [45][46][47][48][49][50][51][52][53]. However, future in vitro work and long-term clinical studies are needed to confirm the antibacterial and anti-inflammatory potentials of these natural molecules.…”
Section: Discussionmentioning
confidence: 99%